Changes in EEG Brain Connectivity Caused by Short-Term BCI Neurofeedback-Rehabilitation Training: A Case Study - Wang, Youhao; Luo, Jingjing; Guo, Yuzhu; Du, Qiang; Cheng, Qiying; Wang, Hongbo (Frontiers in Human Neuroscience, 2021)
Background: In combined with neurofeedback, Motor Imagery (MI) based Brain-Computer Interface (BCI) has been an effective long-term treatment therapy for motor dysfunction caused by neurological injury in the brain (e.g., post-stroke hemiplegia). However, individual neurological differences have led to variability in the single sessions of rehabilitation training. Research on the impact of short training sessions on brain functioning patterns can help evaluate and standardize the short duration of rehabilitation training. In this paper, we use the electroencephalogram (EEG) signals to explore the brain patterns' changes after a short-term rehabilitation training. Methods: Using an EEG-BCI system, we analyzed the changes in short-term (about one-hour) MI training data with and without visual feedback, respectively. We first examined the EEG signal's Mu band power's attenuation caused by Event-Related Desynchronization (ERD). Then we use the EEG's Event-Related Potentials (ERP) features to construct brain networks and evaluate the training from multiple perspectives: small-scale based on single nodes, medium-scale based on hemispheres, and large-scale based on all-brain. Results: Results showed no significant difference in the ERD power attenuation estimation in both groups. But the neurofeedback group's ERP brain network parameters had substantial changes and trend properties compared to the group without feedback. The neurofeedback group's Mu band power's attenuation increased but not significantly (fitting line slope =0.2, t-test value p>0.05) after the short-term MI training, while the non-feedback group occurred a insignificant decrease (fitting line slope=-0.4, t-test value p>0.05). In the ERP-based brain network analysis, the neurofeedback group's network parameters were attenuated in all scales significantly (t-test value: p<0.01); while the non-feedback group's most network parameters didn't change significantly (t-test value: p>0.05). Conclusion: The MI-BCI training's short-term effects does not show up in the ERD analysis significantly but can be detected by ERP-based network analysis significantly. Results inspire the efficient evaluation of short-term rehabilitation training and provide a useful reference for subsequent studies.